Little reporters club: a milestone of innovation - Loo, Mee Lan; Loo, Lek Fong; Loo, Beng Guat; Lau, Su Xiu; Chan, Choon Tak (Universiti Teknologi MARA, Kedah, 2018)
Nowadays, education plays an essential role in developing the next generation of innovators and creative thinkers. Therefore, SJKC Taman Connaught had founded the Little Reporters Club (Kelab Redaksi) in 2008 as part of an innovative scheme by the school resource centre. The club offers a variety of interesting activities to exploit the hidden talents of the pupils. In the meantime, the pupils also acquire a set of soft skills that will help them to improve their self confidence in communicating with others as well as the art of presentation in order to become outstanding reporters in the near future. All these are possible due to various innovative programs such as educational camps, workshops, school trips and other exciting activities conducted by the school resource centre. On the whole, the Resource Centre of SJKC Taman Connaught are targeting to produce holistic individuals and developing them to their full potential and fulfill the aspirations of the nation. Novelty and uniqueness: The club‟s innovative teaching and training strategies through various methods such as learning camps, workshops, and educational hands-on experience that produce a batch of outstanding little reporters that can speak and write confidently in THREE languages i.e. Mandarin, English and Malay with some of their masterpieces published in the school magazines and editorials.